Vasopressin and Oxytocin Reduce Food Sharing Behavior in Male, but Not Female Marmosets in Family Groups - Taylor, Jack H.; Intorre, Allison A.; French, Jeffrey A. (Frontiers in Endocrinology, 2017)
Oxytocin is critical for lactation and maternal care, but oxytocin and the related nonapeptide vasopressin are important for caregiving behaviors in fathers and alloparents as well. This experiment tested the effects of vasopressin and oxytocin on food sharing in marmoset families. We treated caregivers (parents, siblings) with intranasal vasopressin, oxytocin, or saline, and then paired them with the youngest marmoset in the family. Caregivers were given preferred food, and then observed for food sharing and aggressive behavior with young marmosets. Oxytocin reduced food sharing from male alloparents to youngest siblings, and fathers that received vasopressin refused to share food with their youngest offspring more often than when treated with oxytocin. Vasopressin increased aggressive vocalizations directed toward potential food recipients in all classes of caregivers. These results indicate that vasopressin and oxytocin do not always enhance prosocial behavior: modulation of food sharing depends on both sex and parental status.